2023
DOI: 10.1186/s12935-023-02957-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination effects of amino acid transporter LAT1 inhibitor nanvuranlat and cytotoxic anticancer drug gemcitabine on pancreatic and biliary tract cancer cells

Abstract: Background Cytotoxic anticancer drugs widely used in cancer chemotherapy have some limitations, such as the development of side effects and drug resistance. Furthermore, monotherapy is often less effective against heterogeneous cancer tissues. Combination therapies of cytotoxic anticancer drugs with molecularly targeted drugs have been pursued to solve such fundamental problems. Nanvuranlat (JPH203 or KYT-0353), an inhibitor for L-type amino acid transporter 1 (LAT1; SLC7A5), has novel mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…STC-15 (S TORM Therapeutics, NCT05584111) has begun to be tested in the clinic, which is the first RNA epigenetic anti-cancer drug project moving into clinical trials in the world. Moreover, SLC7A5 inhibitors R-OKY-034F (PRN-jRCT2051200105, JPRN-UMIN000036395, JPRN-jRCT2051190003) and Nanvuranlat (JPRN-UMIN000016546, JPRN-UMIN000034080) are also under clinical development or have been completed clinical trials (Nishikubo et al 2023 ). Altogether, our data identify METTL3/ALKBH5 and SLC3A2/SLC7A5 as the potential therapeutic targets and pave the way for future development of therapy for bladder cancer related to PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…STC-15 (S TORM Therapeutics, NCT05584111) has begun to be tested in the clinic, which is the first RNA epigenetic anti-cancer drug project moving into clinical trials in the world. Moreover, SLC7A5 inhibitors R-OKY-034F (PRN-jRCT2051200105, JPRN-UMIN000036395, JPRN-jRCT2051190003) and Nanvuranlat (JPRN-UMIN000016546, JPRN-UMIN000034080) are also under clinical development or have been completed clinical trials (Nishikubo et al 2023 ). Altogether, our data identify METTL3/ALKBH5 and SLC3A2/SLC7A5 as the potential therapeutic targets and pave the way for future development of therapy for bladder cancer related to PAHs.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, it was shown that JPH203 (nanvuranlat), a selective inhibitor of LAT1, suppressed pancreatic cancer cell proliferation and tumor growth, alone and in combination with gemcitabine. 13 , 14 The results indicated that the inhibition of LAT1 downregulated global translation in pancreatic cancer cells through the amino acid signaling mediated by mTORC1 and general amino acid control (GAAC) pathways. In the clinical setting, JPH203 was tested in a phase 1 study involving 17 patients with solid tumors, including 4 with pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%